Determinan Partisipasi Pekerja Perempuan Pada Pasar Tenaga Kerja Di Sumatera Barat - Ravyka Fajri Utami; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to determine the effect of age, education level and marital status on the status of women workers in West Sumatra Province. This type of research is descriptive quantitative. Types and sources of data from the National Labor Force Survey (SAKERNAS) in 2019. The analytical method used is Logistic Regression to see the effect of the dependent variable on the independent variable and the number of samples used is 14143 female workers. The results showed that (1) Age had a positive and significant effect on the status of female workers in West Sumatra Province. (2) Education level has a negative and significant effect on the status of women workers in West Sumatra Province. (3) Marital status has a negative and significant effect on the status of female workers in West Sumatra Province.